Extended Data Figure 2 – Source Data (anxiety-like behavior in the open-field test) - Jinseon Yu (22598699) (2025)
This dataset contains the raw numerical values used to generate Extended Data Figure 2, which examines anxiety-like behavior in the open-field test (OFT) following repeated ketamine administration. Included data: - Quantification of time spent in the outer zone and center zone of the open field (Panel 2b) - Number of entries into the center zone for each mouse (Panel 2b) Structure: - The worksheet includes per-mouse measurements for outer-zone time, center-zone time, and center-zone entries. - All values represent unprocessed raw data directly used to generate the plots in Extended Data Figure 2. This dataset provides the numerical values underlying the analysis shown in Extended Data Figure 2